1995
DOI: 10.1111/j.1365-2133.1995.tb02662.x
|View full text |Cite
|
Sign up to set email alerts
|

Irritant susceptibility and weal and flare reactions to bioactive agents in atopic dermatitis. II. Influence of season

Abstract: Many atopic dermatitis (AD) patients have exacerbations of their skin disease in winter. These exacerbations may be caused by non-immunological 'non-specific' factors, such as low sun exposure and low temperature. To date, the influence of season on non-specific skin reactivity in AD has not been studied. The aim of the present investigation was to assess the influence of season on two skin parameters which may be used as quantitative measures of non-specific skin reactivity in AD: (i) susceptibility to repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 21 publications
3
26
0
3
Order By: Relevance
“…As regards TEWL, Tupker et al [13] found an increase in the winter in both a normal control group and a group of volunteers suffering from atopic dermatitis. The greatly increased winter TEWL found in the present study reflects the poor state of the stratum corneum, characterized by xerosis, loose structure, cracks in the stiff stratum corneum and scratches induced by the incessant itching associated with winter xerosis in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…As regards TEWL, Tupker et al [13] found an increase in the winter in both a normal control group and a group of volunteers suffering from atopic dermatitis. The greatly increased winter TEWL found in the present study reflects the poor state of the stratum corneum, characterized by xerosis, loose structure, cracks in the stiff stratum corneum and scratches induced by the incessant itching associated with winter xerosis in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Higher irritability of the skin in winter has been reported not only in healthy [1,2] but also in atopic subjects [3]. We often hear complaints even from healthy females that their facial skin becomes more irritable during winter.…”
Section: Introductionmentioning
confidence: 99%
“…En ISAAC I se encontró una relación negativa con el consumo de verduras, proteinas de cereales, frutos secos y pescado fresco (17,18,19), basándo-se en posibles alteraciones dietarias y disponibilidad de araquidonatos en las membranas celulares (20)(21)(22)(23). Este es un cofactor que estamos analizando en conjunto los participantes del estudio ISAAC III.…”
Section: Discusión Y Conclusionesunclassified